Ecoagriculture : strategies to feed the world and save biodiversity - McNeely, Jeffrey A. (Island Press, 2003)
McNeely (chief scientist, IUCN-The World Conservation Union) and Scherr (advisor, Future Harvest-Washington, D.C.) argue that the maintenance of biological diversity can be compatible with increased agricultural yield. They detail 36 case studies that suggest farmers can gain economic benefits in farming systems that promote biodiversity. Technological innovation is a primary key to the promotion of "ecoagriculture." They provide separate recommendations for areas where the top priorities are maintaining biodiversity, improving agricultural productivity, or promoting poverty reduction